Improving The Quality Of Steel Plate Finishing Process Using Six Sigma, FMEA, And QFD Methods - Novantoro, Irwan; Abdullah, M. Hasan; Riyanto, Ong Andre Wahyu; Purnamayudhia, Onny; Hindratmo, Astria; Suwondo, Ampar Jaya (Faculty of Engineering, Wijaya Putra University, 2024)
XYZ is a manufacturing company engaged in the hot rolled steel plate rolling mill industry. The results of the finishing production report show that the finishing line process has the highest proportion of defects compared to gas cutting plates ( flare cutting ). This study identifies the causes and solutions for repairing defects in the finishing line using the Six Sigma and FMEA-QFD methods. Based on the initial calculation results, it was obtained that the sigma level and DPMO value were 3.28 and 37,821. From the results of the Pareto diagram, there are five types of defects, namely chamber, BC (bad cutting), BE (bad edge), handling, and OOS (out of square) . The dominant type of defect is the chamber with a percentage of 31.9%. Factors causing defects include operator fatigue, lack of discipline, poor lighting, less than optimal maintenance, knife quality, worn sideguards , and materials. The results of the FMEA analysis show three priorities for proposed improvements, namely, improving operator supervision and SOPs, developing sideguard designs , and knife replacement standards. The development of the sideguard design uses the QFD method, which produces specifications in the form of integrated roll with a distance of 600mm, sideguard dimensions of 6096x200 millimeters with a thickness of 16mm, and made of ASTM A36 steel. The improvements made showed a more stable process with a decreasing number of chamber defects and increasing the Sigma Level value to 3.4 .